Voice Collection under Different Spectrum - Min Li; Yu-duo Wang (Institute of Advanced Engineering and Science, 2013)
According to the short-time Fourier transform theory and principle of digital filtering, this paper established a mathematical model called collection of voice signal collection at different spectrum. The voice signal was a non-stationary process, while the standard Fourier transform only applied to the periodic signal, transient signals or stationary random signal. Therefore, the standard Fourier transform could not be directly used for the speech signal. By controlling the input different types and parameters, this paper analyzed the collected original voice signal spectrum with the use of MATLAB software platform. At the same time, it realized the extraction, recording and playback of the speech signal at different frequencies. Therefore, the waveforms could be displayed obviously on the graphic user interface and voice effect could be more clearly. Meanwhile, the result was verified by the hardware platforms, which consisted of TMS320VC5509A [1] chip and TLV320AIC23 voice chip. The results showed that the extraction of voice signal under different spectrum model was scientific, rational and effective. http://dx.doi.org/10.11591/telkomnika.v11i5.2498